PENYULUHAN MENGENAI PERBEDAAN PSIKOLOGI SUAMI-ISTRI - Lail, Jamalul (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
Good and harmonious relationship between husband and wife does not just happen. It requires a great effort from both sides. In some cases, most of young marriage couples have not been able to understand deeply about the role and duties of being marriage. Therefore, there should be education about the psychology of husband and wife, especially in the dusun Sentono, which has a lot of young marriage couples.